Study of Organoleptic Properties and Nutritional Content of Banana Brownies AS Healthy Snacks for School Children - AASP Chandradewi; Novia Maulida; Made Darawati; Luh Suranadi (Poltekkes Kemenkes Mataram, 2023)
Background: Snacks can help meet the nutritional needs of children who do not bring food to school. However, many snacks circulating in the community still need to be guaranteed for their safety or nutritional content. Efforts are required to meet nutritional needs by developing a product in the form of brownies as a healthy snack for school children using local food in the form of Ambon bananas as a substitute in making brownies. This research aims to determine the organoleptic properties and nutritional content of banana brownies as a healthy snack for school children.Research Methods: This study used an experimental method in the laboratory with a completely randomized design (CRD). Ambon banana puree substitution was carried out with three levels of treatment (25%, 50%, and 75% of the total flour), with three repetitions. Data on organoleptic properties were collected by organoleptic test using the hedonic method and statistically analyzed using Analysis Of Variance (One Way Annova) at the 95% confidence level (α = 0.05). Research Result: The results of the study of the organoleptic test of banana brownie products with 25% Ambon banana puree substitution of total wheat flour (20 grams) obtained a significant texture (≤ 0.05), while color, aroma, and taste were not substantial (> 0.05). Conclusion: The study of the organoleptic properties of banana brownies found that panelists preferred the treatment level, namely t1 (substitution of Ambon banana puree 25% of total flour). The nutritional value in 1 serving of 100 grams of banana brownies is 402.9 kcal of energy and 6.8 grams of protein.